Severity-Level Stratification and Robson Ten-Group Classification of Caesarean Sections at a Tertiary Referral Hospital in West Sumatra, Indonesia: A Cross-Sectional Study - Muhammad Farhan Hawari; Aladin; Husnil Kadri (Archives of The Medicine and Case Reports, 2026)
Caesarean section rates have risen worldwide, and the World Health Organization endorses the Robson Ten-Group Classification System as the global standard for facility-level audit. Severity-stratified Robson data remain scarce in Indonesia, and none exist for central Sumatra. This cross-sectional census characterised the clinical-severity distribution and Robson classification of caesarean sections at RSUP Dr. M. Djamil, the sole tertiary (type A) referral hospital for central Sumatra, during 2021. All 679 deliveries were reviewed by total sampling; 560 (82.47%, 95% CI 79.43–85.15) were caesareans, a fraction reflecting the apex-referral casemix rather than population practice. Proportions were estimated with Wilson confidence intervals, distributions tested by goodness-of-fit chi-square with Cohen's w, and indicators benchmarked against national and WHO standards. Severity level II predominated (48.93%, 95% CI 44.81–53.06), with level I (47.86%) and level III (3.21%) (chi-square=228.700, p<0.001, w=0.639). Robson Group 10 was largest (30.19%, 95% CI 26.86–33.75), followed by Group 5 (21.80%) and Group 2 (15.02%); Groups 5 and 10 together contributed 51.99%. Group 10 exceeded the Indonesian mean of 14.20% (prevalence ratio 2.13, 95% CI 1.90–2.38, p<0.001). Preterm single-cephalic pregnancies dominate this casemix and represent the priority target for severity-stratified caesarean audit and preterm-referral optimisation in Indonesian tertiary obstetric practice.